From IgG Fusion Proteins to Engineered-Specific Human Regulatory T Cells: A Life of Tolerance - Scott, David W. (Frontiers in Immunology, 2017)
Recent efforts have concentrated on approaches to expand and “specify” human Tregs, and to apply them to modulate adverse immune responses in autoimmunity and hemophilia. We have used retroviral transduction of specific T-cell receptor, single chain Fv or antigen domains in regulatory T cells to achieve this goal. Each of these approaches have advantages and disadvantages. Results with these engineered T cells and evolution of the research developments and paths that led to the development of specific regulatory approaches for tolerance are summarized.